The Cost Management In Education (A Site Study At SMK Negeri 1 Boyolali) - Suyatna, Suyatna (2012)
This study has three aims. First, to describe the characteristics of planning of education costs; second, to describe the realization of education cost; third, to describe the accountability of education costs at SMK Negeri 1 Boyolali. It was a qualitative research using ethnography design. This study was done at SMK Negeri 1 Boyolali with the informant consisting of the principal, treasurer, and teachers. Data collection method used in-depth interview, observation, and documentation. Data analysis used an interactive model of analysis. The findings showed that (1) the activity of planning the educational cost at SMK Negeri 1 Boyolali consisted of three essential components, related to the sourcing cost of education, the preparation of need identification, and educational cost budget. Preparation of educational cost planning was done by considering the results of school's self-evaluation. Meanwhile, the budget prepared for a variety of school activities referring to the eight national standards of education and International vocational school profile using priorities. (2) Realization of the cost of education was done in accordance with the planning prepared, that was based on the principle of school financial management, Value for money (economical, efficient, and effective), accountability, transparency, fairness and integrity. It was used for the improvement of education facilities, new students' admission activities, extracurricular, and employee salaries, and teacher professional development. There are 3 forms of supervision in the realization of the cost of education, in the form of monitoring, auditing and control. With the supervision, it is expected that the cost of education can be used effectively in accordance with the regulations. (3) Accountability for educational cost was realized in the form of tuition fees compiled systematically by the treasurer of activities, school treasurer, and principal. Accountability report submitted each quarter, semester and yearly. In accountability report of educational cost, elaborated on various matters related to the receipt, expenditure, the routine use of financial resources, and be accompanied by evidence of expenditure. Data reported were the same data that were recorded in the general ledger.